The Radiology Characteristic of Pleural Thickening Lesion: Mesothelioma Compared to the Other Pleural Diseases - Majdawati, Ana (Universitas Muhammadiyah Yogyakarta, 2018)
Mesothelioma is a malignancy pleural mass characterized by pleural thickening, that difficult to distinguish from other pleural disorders, such as infection, asbestosis, pleural effusion/empyema. This case report is interesting and important because chest x-ray and chest CT have characteristics of pleural abnormalities that can be used as guidelines for the diagnosis of Mesothelioma. A 56 years old woman with cough, chest pain and breathlessness since a few days ago, and it was getting worse. In the chest auscultation, vesicular voices weaken in both lungs. In chest x ray finding a thin opacity on both hemithorax. The left sinus costophrenicus was blunt. Chest CT finding a pleural thickening in the posterobasal of the chest wall and disseminating to the mediastinum â€“paraaortic and found an osteodestruction of rib bones. Pleural thickening is circumferensial, lobulated, irregular nodular opasities and calsification. The histopathology is malignant epitheloid cell forms a cohesive nest, glandular structure and a lot of micropapillae in accordance with malignant mesothelioma. Malignant pleural thickening has lesion characteristic of â€œirregular nodular opacitiesâ€ on the periphery with or without pleural effuse in chest x ray and in chest CT shows the form of lesions are circumferential, lobulated, encase lung parenchyma.